Caracterização mecânica e morfológica de compositos com fibras de vidro e palha da costa (Raphia Taedigera Mart) - TAVARES, Arthur Ruan Dias (2019)
In this work we were produced composite materials isophthalic polyester matrix with glass fiber insert and the coast straw fibers in lengths of 15, 30 and 45 mm. The composites were made according to the hand lay-up method. For each test seven (7) test bodies were produced for each composition. The matrix used was the isophthalic polyester resin, using initiator (1.0% v / v) and cobalt accelerator (1.5% v / v). The inserted fibers had mass fraction values of 2.5 and 5%. Physical tests were conducted for water absorption, porosity and bulk density apparent adopting NBR 12766, tensile testing of composites according to ASTM D 3039, flexural test according to ASTM D 790 and analysis of the fracture surface by electron microscopy of scanning - SEM. The results showed that there was an increase in the tensile strength limit of the fiberglass composites in relation to the full matrix. The best tensile strength limit results were 21.25 MPa for glass fibers; 9.20 MPa for straw fibers from the coast; the flexural strength for composites with glass fibers was 85.83 MPa, and for composites of straw the coast was 45.65 MPa. The morphological analysis of the fracture surfaces were efficient for the determination of failure mechanisms and features present in the material, where the phenomena of fibers arranged transversely in the direction of loading and broken fibers were observed. The materials produced and characterized presented similar mechanical properties with the literature.